Wracking the Stereotype: Freedom Expression in Woman on "Man! I Feel Like a Woman!" Shania Twain Song's Lyric - Simanjuntak, Juni Santa; Sinaga, Muhammad Hidayatullah Tuahta; Trifena, Atalya; Rangkuti, Rahmadsyah (Kajian Linguistik dan Sastra, 2025)
This study analyzes the song "Man! I Feel Like a Woman!" by Shania Twain using Sara Mills' feminist stylistic theory of three linguistic levels, namely words, phrases, and discourse to explore the lyrics that try to wrack various stereotypes attached to women, especially freedom of expression. This study uses a descriptive-qualitative method and explain the results on the word, sentence, and discourse level. Word-level analysis reveals generic pronouns and nouns emphasizing collective female identity. The phrase level reveals ready-made phrases, presuppositions and inferences, metaphors and transitive choices such as material, mental, relational, and existential that illustrate various aspects that wrack stereotypes against women. Discourse-level analysis reveals characterization, focalization, and schemata that provide deeper insight into the perspectives of the characters in the song. Overall, three-level analysis are in line with feminist principles, emphasizing to wracking stereotypes of freedom expression against women as the main theme. Abstrak Studi ini menganalisis lagu "Man! I Feel Like a Woman!" oleh Shania Twain menggunakan teori gaya feminis Sara Mills dari tiga tingkat linguistik, yaitu kata-kata, frasa, dan wacana untuk mengeksplorasi lirik yang mencoba merobek berbagai stereotip yang melekat pada perempuan, terutama kebebasan berekspresi. Penelitian ini menggunakan metode deskriptif-kualitatif dan menjelaskan hasilnya pada tingkat kata, kalimat, dan wacana. Analisis tingkat kata mengungkapkan kata ganti dan kata benda generik yang menekankan identitas perempuan kolektif. Tingkat frasa mengungkapkan frasa siap pakai, praanggapan dan kesimpulan, metafora dan pilihan transitif seperti material, mental, relasional, dan eksistensial yang menggambarkan berbagai aspek yang merusak stereotip terhadap perempuan. Analisis tingkat wacana mengungkapkan karakterisasi, fokalisasi, dan skema yang memberikan wawasan lebih dalam tentang perspektif karakter dalam lagu. Secara keseluruhan, analisis tiga tingkat sejalan dengan prinsip-prinsip feminis, menekankan pada stereotip kebebasan berekspresi terhadap perempuan sebagai tema utama.